2000
DOI: 10.1046/j.1365-2036.2000.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole provides improved acid control vs. omeprazole in patients with symptoms of gastro‐oesophageal reflux disease

Abstract: Esomeprazole provides more effective acid control than omeprazole, with reduced interpatient variability, thereby offering the potential for improved efficacy in acid-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
216
5
11

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(238 citation statements)
references
References 16 publications
6
216
5
11
Order By: Relevance
“…The AUC of esomeprazole in people has been reported to be higher than that of omeprazole of the same dose 3. The efficacy of esomeprazole in suppressing gastric acid is closely related to the subject's total exposure to the drug (ie, the AUC), and for that reason, esomeprazole has been shown to result in better acid suppression than omeprazole of equal doses in human studies 3, 5, 6, 25, 26. This difference in efficacy between the current study and a previous study may be due to the higher AUC for esomeprazole than for omeprazole, and the difference in study design and formulations (enteric‐coated granules versus a delayed‐release tablet), or it may due to the small study population and inclusion of only 1 breed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The AUC of esomeprazole in people has been reported to be higher than that of omeprazole of the same dose 3. The efficacy of esomeprazole in suppressing gastric acid is closely related to the subject's total exposure to the drug (ie, the AUC), and for that reason, esomeprazole has been shown to result in better acid suppression than omeprazole of equal doses in human studies 3, 5, 6, 25, 26. This difference in efficacy between the current study and a previous study may be due to the higher AUC for esomeprazole than for omeprazole, and the difference in study design and formulations (enteric‐coated granules versus a delayed‐release tablet), or it may due to the small study population and inclusion of only 1 breed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…19 More recently, it has been reported that oral and intravenous pantoprazole are also equivalent, even when administered at a high dose (280-290 mg daily) in healthy volunteers, comparable to doses used for the management of upper gastrointestinal tract haemorrhage (80 mg bolus, followed by an infusion of 8 mg/ h). 19,20 This study was conducted in healthy subjects, and the results should therefore be extrapolated with caution to patients in an intensive care unit (ICU) and those who are being treated for upper gastrointestinal bleeding. The baseline pH data indicate that all subjects had normal gastric secretory function, unlike some ICU patients in whom gastric acid secretion may be compromised by severe concomitant illness.…”
Section: Discussionmentioning
confidence: 99%
“…On further detailed evaluation during the abstraction process, one of these studies was found to have been carried out without blinding and was excluded, 12 two were found to have a Jadad score of only two and were excluded from further analysis 13,29 and one study's primary outcome was based on surrogate end-points (intra-oesophageal pH) and was also excluded. 18 The findings from the systematic review of the remaining 32 studies are summarized and presented in Tables 4-8. The focused clinical questions that had been formulated prior to the search were then addressed using these data.…”
Section: Resultsmentioning
confidence: 99%